Peran Media Sosial Dalam Pencegahan Anemia Pada Remaja Putri - Agustina Widayati; Umi Narsih (CV. Multi Kreasi Media, 2025)
Anemia education can be implemented through various methods, such as health promotion. Health promotion can be promoted through the internet. Currently, many teenagers use the internet to obtain information through social media. Online services are readily available. The availability of internet cafes, laptops, and mobile phones makes it easier for the younger generation to access the internet. A 2016 survey by the Indonesian Internet Service Providers Association (APJII) showed that 132.7 million Indonesians, or approximately 51.8% of the population, use internet services. Internet users aged 10-24 years old account for 75.5% of all teenagers aged 10-24 years. The majority of internet users, at 97.4%, use social media. Anemia can have negative impacts on adolescent girls, including stunted growth, increased susceptibility to infection, decreased physical fitness, and decreased concentration in learning. If anemia is not treated during adolescence, it can lead to maternal mortality, premature births, low birth weight (LBW) and stunted offspring in adulthood. The goal of this Community Partnership Program is to educate young women about the proper use of social media to obtain information about anemia, especially among adolescents. The method used is a collaboration with the Darul Ulum Kraksaan Islamic Boarding School to provide education on early detection of anemia in young women. The success indicator of this activity is an increase in young women's behavior in seeking health information, especially regarding anemia prevention. This activity has run smoothly and has achieved positive benefits, starting with increased enthusiasm among young women in practicing the role of social media in anemia prevention.